OVERVIEW ON RENAL CELL CARCINOMA - SHANKHAJIT DE; SAROJ SINGHMURA; AJOY KUMAR GHOSH (International Journal of Pharma and Bio Sciences, 2010)
Cancer is a disease with uncontrolled multiplication and spread within the body of abnormal forms of the body’s own cell. Renal-Cell Carcinomas (RCC) arises from the renal epithelium and account for about 85 percent of renal cancers accounting approximately 95000 deaths every year. Various types of renal carcinoma are conventional or clear-cell renal-cell carcinoma, papillary renal-cell carcinoma, oncocytoma, chromophobe renal-cell carcinoma, and collecting-duct renal-cell carcinoma. End-stage renal disease (ESRD) increases incidence of cancer at various sites. Common symptom of RCC is flank or abdominal pain, gross hematuria, and an abdominal mass, weight loss etc. Treatment of RCC includes surgery, chemotherapy, immunotherapy, stem cell transplant, tumor vaccine etc. Some molecular targeted therapies are also being used and many are under clinical trials. Diabetes, hypertension, tobacco addiction increases the probability of RCC while the green vegetables, fruits Ca++ supplements, vitamin E reduces the risk.